The Personality of the Main Character, Hemachandra, in the Novel Bandung After Rain: A Study Based on Sigmund Freud’s Theory - Nurul Zuniar Syafitri; Resdianto Permata Raharjo (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2026)
An in-depth analysis of the psychological complexity of a novel’s protagonist is essential because it reflects the inner struggles experienced by individuals in real life. Using a psychoanalytic perspective, this study examines the psychological structure of Hemachandra, the main character in Wulan Nur Amalia’s Bandung After Rain, based on Sigmund Freud’s theory. The study aims to (1) describe the manifestation of the id as an instinctual drive, (2) explain the role of the ego as the executor of reality, and (3) analyse the superego as the controller of morality. This research employed a qualitative descriptive approach, with the novel serving as the primary data source. The researcher acted as the main instrument, applying reading and note-taking techniques for data collection and descriptive-analytical methods for data analysis. The findings reveal that the id is expressed through the pleasure principle, selfish thinking, instinctual impulsivity, and spontaneous aggression. The ego is reflected in self-control, defence mechanisms, ambivalence, and adaptation to reality, while the superego appears through remorse and the internalisation of moral values. The analysis identified 40 data points, dominated by ego aspects (62.5%), followed by the superego (20%) and the id (17.5%). Through data reduction, 13 representative data points were selected for detailed analysis, consisting of 6 id, 5 ego, and 2 superego data points. Overall, the findings indicate that the protagonist’s psychological development is dominated by the ego, suggesting a progression toward greater personality maturity.